Exploring in Setting a Model for Islamic Supply Chain in Malaysia - Saifudin, Adam Mohd; Othman, Siti Norezam; Elias, Ezanee Mohamed (International Review of Management and Marketing, 2017)
This conceptual paper is endeavored to explore critical factors of the Islamic supply chain in Malaysia. Based on an extensive literature review, there are thirteen critical factors to be considered in order to be successfully set a model for Islamic supply chain in Malaysia. The factors are (1) halalan toyyiban rules and policies; (2) supports from government and private; (3) halal hub; (4) differentiation between Muslim and non-Muslim suppliers; (5) halal control and labeling; (6) logistics control; (7) halal quality control; (8) supply chain resources; (9) halal supply chain business process; (10) supplier network structure; (11) halal supply chain performance; (12) JAKIM certification process; (13) halal traceability and tracking system. All the critical factors will be considered in developing a new model for Islamic supply chain in Malaysia. Keywords: critical factor, Islamic supply chain, Malaysia. JEL Classification: R41